Ask a New Question
Search
multiply then simplify by factoring if possible
√3 √6=
1 answer
sqrt(3)*sqrt(6)=sqret(3*6)=sqrt(18)=sqrt(9*2)
sqrt(9)=3
sqrt(9*2)=3*sqrt(2)
sqrt(3)*sqrt(6)= 3*sqrt(2)
Ask a New Question
or
answer this question
.
Similar Questions
Multiply and simplify by factoring. Assume that all expressions under radicals represent nonnegative numbers.
∛(y^13 )
0 answers
Simplify the following expression to Scientific Notation: (9×1016)2
(1 point) Responses Multiply exponents to get 18×1032
1 answer
To simplify this expression, 6x4⋅3x2 which would be the correct steps?(1 point)
Responses Multiply 6 x 3 for the numbers; then
1 answer
Simplify this expression and put your final answer in Scientific Notation:
(2.7x10^(5))/(3.2x10^(7)) Step 1: _ the coefficients.
3 answers
more similar questions